Students’ Perspectives on the Use of Moodle for Learning English at Vocational High School - Khalifani Utami (EDUCAFL : Journal of Education of English as Foreign Language, 2023)
This study is aimed at knowing students’ perceptions on the usage of Moodle LMS at Vocational High School (VHS). A survey method, with simple random sampling of 172 students from the state VHS 12 Malang was used. The results showed students’ positive opinions toward learning English via Moodle. It encouraged them to learn English and facilitated student-centered learning. Problems related to technical issues and difficulties in understanding written documents were also discussed in the study.